WORKSHOP PEMASARAN ONLINE MAHASISWA KKN-PPM UNIVERSITAS PGRI ADI BUANA SURABAYA DESA BULANG PRAMBON SIDOARJO - Ira Eko Retnosari (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Online Marketing is also known as a strategy or method to introduce a consumer / public with a brand / products / services of a company / business. Online Marketing or also known as Internet marketing or some people call online advertising. In this case we used a medium that was the Internet. The simplest thing to remembered was, how to innovated continuously so that your product / service can be more easily found on the internet. In the Online Marketing have an important components that must be known by the reader, that are produk, price, place, promotion, people, physical evidence, and process (7 P). It also have ten’s effective strategies way to sell the product as determine the target market, make a website, make a promotion, Build a TOP Rank Website, running email marketing, consultation with the expert, write for conten marketing, blogging and chatting, use instant messager (E-mail), and mobile messager (BBM,Line,and Whatsapp). The discussion on this article was online marketing in Bulang village received good response from businessmen and villager. This was because online marketing was done by a team of online marketing division of KKN-PPM students Adi Buana University PGRI Surabaya can helped Bulang village of as the village of klepon while increasing revenue and income for the Bulang villagers. So, the result of the article of Online Marketing Program activities was success because all of participants can be good participants. and was held on February 5th to 28th, 2017